Development of a culturally enhanced caregiver-facilitated language nutrition intervention “+Language is Medicine” to address developmental delay in Diné (Navajo) toddlers - Billey, Taylor; Kushman, Elizabeth; Meese, Jessica; Martin, Lisa; Jim, Lisa; Austin-Garrison, Martha A.; Allison-Burbank, Joshuaa D. (Frontiers in Public Health, 2024)
Developmental Delay (DD) is highly common in American Indian & Alaska Native (AI/AN; Indigenous) toddlers and leads to high numbers of AI/AN children who eventually need special education services. AI/AN children are 2.89 times more likely to receive special education compared to other children in the U.S., yet developmental disorders are more frequently under diagnosed and untreated in AI/AN infants and toddlers. DD, which can be identified as early as toddlerhood, can lead to negative impacts on developmental trajectories, school readiness, and long-term health. Signs of DD can be identified early with proper developmental screening and remediated with high quality early intervention that includes effective parent training. There are many evidence-based language facilitation interventions often used in Early Intervention programs. However, in communities in rural parts of the Navajo Nation where there are limited services and resources, infants and toddlers with early signs of DD are often missed and do not get the culturally responsive support and evidence-based intervention they deserve.The community-based +Language is Medicine (+LiM) study team partnered with tribal home visitors, community members, and a Diné linguist/elder using a collaborative virtual workgroup approach in 2021 and 2022 to present the +LiM pilot study aims and to discuss strategies for enhancing a language intervention for toddlers experiencing DD in their tribal community.